Production of fuels from plastic waste through chemical recycling processes (Publicaciones en Ciencias y Tecnología, 2023)
Environmental pollution in the world due to plastic waste reaches alarming levels every day; about eight million tons a year of this waste ends up in the oceans. Although the scientific and academic community have tried to develop and apply new methods and technologies to recycle such waste, currently only 15% of the 400 million tons produced annually are recycled. This work aims to present a state of the art on chemical recycling technologies that are available and still in the development stage to produce fuels from plastic waste. The bibliographic review technique was applied to locate the information of the articles and patent applications published in the period 2012-2022; coupled with the Content Analysis technique to process and analyze the information; as well as bibliometrics to obtain the main trends in the area. Among the most important challenges presented by these technologies is that most require high energy consumption and some only process homogeneous waste.
Keywords: Fuel production; plastic waste; waste recycling; conversion processes; trends